The Turkish adaptation of leisure facilitator scale: a validity and reliability study - B. Gürbüz; E. Öncü; E. Emir (Physical Education of Students)
Purpose: The aim of this study to test the reliability and validity of “Leisure Facilitator Scale” (LFS) for Turkish university students. Material: The sample included 111 female and 132 male, and totally 243 faculty of sport sciences’ students for this study. The LFS which was consists of 3 subscales and 27 items was used to collect data. Besides descriptive statistics, confirmatory factor analysis was applied to test the factor structure of LFS. Pearson’s product-moment coefficients were used to examine correlations between the factors. For determining the reliability of the scale Cronbach Alpha coefficient was calculated. Results: Analysis indicated that the Turkish version of the LFS constituted of 3 subscales and 16 items. Totally 11 items were excluded from the Turkish version because of lower factor loadings. Factor loading values of the items ranged between 0.49 and 0.76. Cronbach Alpha values were calculated as 0.79, 0.66, 0.78 and 0.86 for the subscales and total scale respectively. Conclusions: In conclusion, results indicated that “Leisure Facilitator Scale” Turkish adapted form can be used as a valid and reliable measurement tool to examine the factors that facilitate leisurely participation of students.